Kajian Daya Dukung Ekowisata Hutan Mangrove Blanakan, Subang, Jawa Barat - Muhammad, Fuad; Basuni, Sambas; Munandar, Aris; Purnomo, Herry (Bioma : Berkala Ilmiah Biologi, 2012)
Growth in tourist arrivals at ecotourism mangrove in Blanakan can cause a threat to the preservation of conservation areas and tourist attraction. This happens when the utilization of the region exceeds its carrying capacity. The aims of This study  to identify the carrying capacity of ecotourism mangrove in Blanakan as conservation areas are used for tourism activities. The results showed that the carrying capacity the ecotourism mangrove in Blanakan is 425 visitors per day. Pollution load simulation results showed that ecotourism mangrove Blanakan  had suffered pollution by phosphate, ammonia pollution carrying capacity will be passed  in 2019 and organic waste in the year 2011 to 2013, while nitrate and garbage until the year 2032 has not been exceeded.   Key words: ecotourism, mangrove, carrying capacity